Successful radiofrequency catheter ablation of Wolff-Parkinson-White syndrome in a patient with dextrocardia: A case report - Zhao, Lei; Li, Ruibin; Bai, Long; Wang, Dong; Zhang, Jidong; Yang, Xiaohong (Frontiers in Cardiovascular Medicine, 2022)
Abstract Background Dextrocardia is an uncommon congenital malposition that occurs in only 1 in 10,000–12,000 humans.Wolff-Parkinson-White (WPW) syndrome is an inborn condition with an additional accessory pathways between the atria and the ventricle which affects up to three in 1,000 people worldwide.Experience of radiofrequency catheter ablation in patients with Wolff–Parkinson–White syndrome and dextrocardia is limited for its extremely rare incidence. Case presentation An 39-year-old female was hospitalized due to two episodes of palpitations in the latest two months.The morphology of P-QRS-T complex of lead aVR and aVL, II and III were presented invertedly as common conditions,and shortened P-R interval and a characteristic “delta” wave were shown on the electrocardiogram (ECG).The patients with dextrocardia and situs invertus malposition was confirmed by chest-X ray,cardiac color Doppler echocardiography.The patient was diagnosed Wolff-Parkinson-White (WPW) syndrome with dextrocardia and underwent radiofrequency catheter ablation successfully. In this particular case,the main challenge of RFCA is to understand the anatomical structure of the heart and the great vessels before the operation and make the strategy. Conclusion Catheter ablation for tachycardia patients with dextrocardia is safe and efficient.For patients with dextrocardia, the key to successful ablation was adjusting for projection angulation and different catheter manipulation compared with a standard case because of the mirror image of a normal heart. Keywords Dextrocardia, Wolff-Parkinson-White (WPW) syndrome, Radiofrequency Catheter Ablation,Tachycardia.